Imaginários do Sul : pensamento crítico de fronteira e os avessos da modernidade na ficção de Aldyr Garcia Schlee - Goulart, Cátia Rosana Dias (2016)
In Imaginaries of the South: critical border thinking and the reverse of modernity in Aldyr Garcia Schlee's fiction, I reflected upon the development of critical thinking in Latin America and its implication in the creation of imaginaries. After analyzing the investigations carried out by researchers who focus on border literature in the south of Brazil, Uruguay and Argentina, I showed how they managed to develop a homogeneous image of the border literature in the region while being connected to the paradigm of transculturation. Taking into account that the imaginary of the local fiction in the region is currently more diversified that critics have shown, I aimed at changing this image. Therefore, I analyzed critical thinking in Latin America from the perspective of readings which have been understood as Border Thinking and interpret Aldyr Garcia Schlee's fictional work. In this way, with intercrossing readings, I showed how the writer invests in the development of an authorial performance and in the use of multiple social memories in his fiction, besides creating a symbolic space which not only provides evidence of the inviability towards restricting regional literature to the gaucha literature but also highlights its interrelation and other regions in the world.